A fever in the heartland : the Ku Klux Klan's plot to take over America, and the woman who stopped them - Egan, Timothy (Viking, 2023)
"A historical thriller by the Pulitzer and National Book Award-winning author that tells the riveting story of the Klan's rise to power in the 1920s, the cunning con man who drove that rise, and the woman who stopped them. The Roaring Twenties -- the Jazz Age -- has been characterized as a time of Gatsby frivolity. But it was also the height of the uniquely American hate group, the Ku Klux Klan. Their domain was not the old Confederacy, but the Heartland and the West. They hated Blacks, Jews, Catholics and immigrants in equal measure, and took radical steps to keep these people from the American promise. And the man who set in motion their takeover of great swaths of America was a charismatic charlatan named D.C. Stephenson. Stephenson was a magnetic presence whose life story changed with every telling. Within two years of his arrival in Indiana, he'd become the Grand Dragon of the state and and the architect of the strategy that brought the group out of the shadows - their message endorsed from the pulpits of local churches, spread at family picnics and town celebrations. Judges, prosecutors, ministers, governors and senators across the country all proudly proclaimed their membership. But at the peak of his influence, it was a seemingly powerless woman - Madge Oberholtzer - who would reveal his secret cruelties, and whose deathbed testimony finally brought the Klan to their knees"--